Work or live? Comments on the Economy of Time in Neoliberalism - Berger, Christian; Ziolkowski, Maria (Momentum Quarterly, 2016)
In Karl Marx’s economy of time, the economy itself disintegrates. Following this vague premise, this article discusses the ambivalences relating work and time. In the center of our treatise, we place the neoliberal gamble with freedom and coercion, emancipation and submission as well as the sociocritical diagnose of proliferation, subjectivisation and flexibilisation of work. Furthermore, we will cast a light on the recent legal, economical and political implications of the genealogy and transformation of working time and their effects on gender structures. Providing theoretical and empirical examples, this article will come to the conclusion that this transformation sets up a form of autonomy which leads to a restriction for and disciplining of individuals according to neoliberal postulation.